2022
DOI: 10.3390/cimb44050145
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin Targets Atherosclerosis: Gene Expression Profiling of THP-1 Macrophages Treated with Punicalagin and Molecular Docking

Abstract: Atherosclerosis is an important cause of cardiovascular disorders worldwide. Natural botanical drugs have attracted attention due to their antioxidant, anti-inflammatory, and antiatherogenic properties in the treatment of atherosclerosis. Punicalagin is the major bioactive component of pomegranate peel, and has been shown to have antioxidant, anti-inflammatory, antiviral, anti proliferation, and anticancer properties. To explore its antiatherogenic properties at a molecular level, we investigated the genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…De acordo com Huwait et al (2022), a punicalagina exerce seus efeitos também a nível molecular, conforme os métodos utilizados foram avaliadas mudanças na expressão gênica de macrófagos THP-1. Entre os testes realizados, foi feita a ancoragem molecular e observado que dos 20 genes estudados todos foram regulados positivamente em relação a atividades da punicalagina.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…De acordo com Huwait et al (2022), a punicalagina exerce seus efeitos também a nível molecular, conforme os métodos utilizados foram avaliadas mudanças na expressão gênica de macrófagos THP-1. Entre os testes realizados, foi feita a ancoragem molecular e observado que dos 20 genes estudados todos foram regulados positivamente em relação a atividades da punicalagina.…”
Section: Resultsunclassified
“…artigos, sendo eles(Benchagra et al, 2021),(Atrahimovich et al, 2016),(Manickam et al, 2022),(Aviram e Rosenblat, 2013),(Huwait et al, 2022),(Anwaier et al, 2021) e apenas 1 em português(Aviram et al, 2000), como apresentado no quadro a seguir (Quadro 1).…”
unclassified
“…Molecular docking is an important method for drug discovery and has become a core computational approach in drug design to predict the binding affinity and provide the interactive mode [ 56 ]. In recent years, molecular docking combined with MD simulation has been utilized to identify the molecular targets of several potential major bioactive components for AS including punicalagin, quercetin and luteolin, which provide a basis for pharmacological research and clinical application for AS [ 57 59 ]. In the current study, we identified compound DB07117 combined with VCL protein stably, which indicated that compound DB07117 was a potential inhibitor of VCL protein.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] The prepared protein structures and the ligand were utilized for the docking. [ 12 ] The docking software employed algorithms to predict the binding orientations and affinities of the ligand within the binding sites of the target proteins. The docking calculations considered various factors, including protein-ligand interactions, shape complementarity, and electrostatic potentials, to generate potential binding poses.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%